How ‘Pro Corporate Cash-Flow Tax’ Design May Promote The Development Of Telecommunication Industry - Rosdiana, Haula (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
Telecommunication industry (‘the industry’) plays an important role in economic growth. Therefore, it is beneficial when the Government prepares policies enhancing the development of this industry. This study offers an alternative design of income tax system namely Pro Corporate Cash-flow Tax (PCCFT). The PCCFT is developed from the angle of Supplyside Tax Policy concept. This policy encourages the private sector to increase its supply of products by possibly removing the provisional withholding tax system (i.e., Art 23 Income Tax).1 As withholding tax on business income absorbs industry’s fund, its removal effectively injects the industry with working capital. In addition thereto, the recharacterization of income may jointly reduce cost of taxation and therefore improving the business climate. This research employs constructivism paradigm with mixed approaches. PCCFT appears to be able to minimize opportunity costs, while offering the industry some advantages (including potential revenue). For the Government, it may increase potential tax revenue as well as non-tax revenue (e.g. radio frequency fee and dividends), universal service obligation fee, penetration facilities and teledencity fees. Moreover, this design may create job opportunities and alleviate poverty as well as improve prosperity.